Critérios de sustentabilidade nas aquisições de bens e contratações de serviços da gestão pública federal - Cogo, Giselle Alves da Rocha (2015)
The goal of this study is to propose the adoption of sustainability criteria in procurement of goods services in the Federal Public Administration, contributing to the improvement of the conceptualization and execution of environmental, economic and social considerations in public contracts, in accordance with internationally accepted principles and practices. In terms of methodology, the research is basic regarding its nature, exploratory regarding its goals and bibliographical regarding its technical procedures. The bibliographical review considered publications from 2009 to 2013, to conceptualize sustainable development, sustainable procurement and economic efficiency, to characterize the implementation of sustainable procurement in Brazil, its restrictive and booster points, evaluating aspects of the legislation that motivate sustainable procurement in public organizations. The adoption of sustainability criteria in government procurement was based on results from bibliographic and documentary research, which corresponds to the first phase of development of the research, which identified sustainability criteria and best practices, and described how the process of property acquisition and services develops. The second phase of work was developed from the knowledge of the definitions of the process and the legal instruments used in the procurement and service contracts of the Federal Public Administration. In this step, the procedure commonly used by public organizations was described. For the inclusion of sustainability criteria in the process, improvement alternatives were proposed from the results obtained in the first phase. The purchasing process of federal public organizations has been rewritten and possible actions for sustainability were included. As the main result, the present work listed sustainability criteria to be adopted in government procurement. It is considered that the legal aspects, the lack of goals and lack of knowledge of managers make the practical application of sustainable procurement in Brazil slow. These actions occur in a timely manner, the supply of sustainable products and services is scarce, there lacks information and training to public managers, besides the need for change in organizational culture. The research sought to present the potential that Sustainable Procurement has, contributing to the promotion of sustainable development, to the improvement of the efficiency and effectiveness of purchases which can positively impact on a country's investment climate, establishing a key indicator of government commitment towards sustainable development.